A Genealogy of Literal Translation in Modern Japan - Mizuno, Akira (TTR)

(untitled) (Association canadienne de traductologie, 2009)
In modern Japan, especially in the Meiji period (1868-1912), translations occupied a dominant position in the literary polysystem. This paper claims that, since the Meiji period, “competing translational norms” have existed in the Japanese literary polysystem, which is to say that “literal” (adequate) and “free” (acceptable) translations have existed in parallel, vying for superior status. Moreover, this paper traces the literalist tradition in modern Japan. Though “literal” translation has been widely criticized, the styles and expressions it created have made a significant contribution to the founding and development of the modern Japanese language and its literature. Among the arguments in favor of literal translation, Iwano Homei’s literal translation strategy—the so-called “straight translation”—had different features than the others, and thus the potential to produce translations that maintain the cohesion, coherence, information structure and illocutionary effects of the source text.